2021
DOI: 10.1007/s11916-021-00943-6
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing New Persistent Opioid Use After Surgery: A Review of Interventions

Abstract: Purpose of Review This review aims to summarize interventions used in the perioperative period to reduce the development of new persistent postoperative opioid use in opioid-naïve patients. Recent Findings The development of new persistent opioid use after surgery has recently been identified as a common postoperative complication. The existing literature suggests that interventions across the continuum of care have been shown to decrease the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…41 Given our finding that women who underwent laparoscopic repair were more likely to receive opioids within 7 days of the surgery than women who underwent vaginal reconstruction and that among those receiving perioperative opioids, rates of new persistent opioid usage did not differ by reconstructive surgical-approach, procedurespecific, evidence-based prescribing guidelines, including the creation of pain management order sets, may help reduce opioid use. 14 Patient-specific protocols, incorporating individual patient assessment, with follow-up assessments as needed for opioid prescribing with instructions to taper before discharge, may also help mitigate persistent postoperative opioid use and individual risk factors. 42 The limitations of this study are those inherent in research driven by a claims database, including patient deidentification, reliance on proper ICD-10 code classification, and lack of adherence and socioeconomic status data.…”
Section: Discussionmentioning
confidence: 99%
“…41 Given our finding that women who underwent laparoscopic repair were more likely to receive opioids within 7 days of the surgery than women who underwent vaginal reconstruction and that among those receiving perioperative opioids, rates of new persistent opioid usage did not differ by reconstructive surgical-approach, procedurespecific, evidence-based prescribing guidelines, including the creation of pain management order sets, may help reduce opioid use. 14 Patient-specific protocols, incorporating individual patient assessment, with follow-up assessments as needed for opioid prescribing with instructions to taper before discharge, may also help mitigate persistent postoperative opioid use and individual risk factors. 42 The limitations of this study are those inherent in research driven by a claims database, including patient deidentification, reliance on proper ICD-10 code classification, and lack of adherence and socioeconomic status data.…”
Section: Discussionmentioning
confidence: 99%
“…ERPs have been shown to be safe and effective, though have been under-utilized across surgical subspecialities. [22][23][24] For example, a recent study of 113 Pediatric Urologists demonstrated that 61% were somewhat familiar or not familiar with standardized ERPs. While 54% utilized some individual ERP elements, only 20% had a complete standardized pathway.…”
Section: Commentmentioning
confidence: 99%
“…While opioids have been the main therapy for acute pain management after major surgery, recent evidence documents that persistent opioid use after surgery represents a risk of opioid use disorder as a common postoperative complication. 21 Many of the current pain management pathways advocate for the use of multi-modal therapy to minimize the need for opioids and their side effects. 22 One study suggests that regional techniques targeting postoperative pain control in hip fracture patients may reduce the likelihood of postoperative delirium.…”
Section: Opioid-sparing Techniques For Postoperative Pain Managementmentioning
confidence: 99%